2011
DOI: 10.3892/etm.2011.415
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of nuclear PA28γ expression in cirrhosis and hepatocellular carcinoma

Abstract: Abstract. We previously reported that proteasome activator 28γ (PA28γ) is an oncogenic protein in hepatitis C virus (HCV) core protein transgenic mice. The aim of this study was to determine the role of PA28γ expression at the protein level in the development and progression of human hepatocarcinogenesis and hepatocellular carcinoma (HCC). Samples from tissues representing a wide spectrum of liver disease were analyzed, including histologically normal livers (n=5), HCV-related chronic hepatitis (CH) (n=15) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…20 The nuclear PA28 γ is involved in the progression and the relapse of hepatocellular carcinoma. 27 It suggested that PA28 γ was a novel serum biomarker for the diagnosis of CRC 28 ; however, the reports above needed further validation by more experimental and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…20 The nuclear PA28 γ is involved in the progression and the relapse of hepatocellular carcinoma. 27 It suggested that PA28 γ was a novel serum biomarker for the diagnosis of CRC 28 ; however, the reports above needed further validation by more experimental and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 26 ] indicated an overexpression of PA28γ in breast cancer and demonstrated a relation of expression with cancer status and metastasis. Kondo et al [ 29 ] mentioned an increase of nuclear PA28γ with the progression of liver disease from hepatitis C virus related chronic hepatitis to liver cirrhosis. These findings suggest PA28γ as target for prevention and/or treatment of hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these functions it seems to be very likely that PA28γ is involved in carcinogenesis. Many studies revealed that PA28γ is overexpressed in different tumor tissues and serum samples of patients with diverse cancers affecting colon [ 24 , 25 ], breast [ 26 ], larynx [ 27 ], lung [ 28 ], liver [ 29 ] and thyroids [ 30 ]. Thus, PA28γ interferes with cell cycle, proliferation and invasion in poorly differentiated thyroid carcinoma cells [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Протеомное [44,45], колоректальном раке [46], гепатоцеллюлярной карциноме [47] и плоскоклеточном раке полости рта [48].…”
Section: убиквитин-протеасомная система при плоскоклеточном раке полости ртаunclassified